The development of Tekat multimedia courseware based on the assure model in Visual Art Education subject / Shahril Harun - Harun, Shahril (2014)
The purpose of this study was to design and develop a computer-assisted courseware on Tekat topic for Form 2 Visual Art Education. This Tekat courseware uses the ASSURE model as a guide. This courseware is developed as an option for Visual Art Education (VAE) teachers to accurately teach the concept of Tekat. The use of graphic videos in teaching the Tekat concept is able to improve VAE teachers’ understandings on Tekat which is rather difficult to be produced manually. Furthermore, this courseware also provides an interactive self-learning environment for the VAE teachers. Findings from this study found that the VAE teachers were interested to use the Tekat courseware in the learning and teaching process in classrooms. By combining the multimedia courseware in the learning and teaching process, the VAE teachers also showed a positive effect on their motivation to teach the Tekat topic more effectively. This study also showed that the Tekat art is one of the traditional crafts that has to be preserved as a symbol of arts among the Malay society.